2018
DOI: 10.4236/ojpathology.2018.83013
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Combined; Cox-2, Cyclin D1 and P21 Expression in Colorectal Cancer (CRC) Patients: An Immunohistochemical Study

Abstract: Background: Cyclooxygenase (COX) is a rate limiting enzyme in synthesis of prostanoids pathway and it has 2 isoforms (COX-1 and COX-2). It has many biological roles in inflammation and oncogenesis. Cox-2 was incriminated in performing disturbances in the cell cycle control in CRC, but its role of in CRC needs clarification of the mechanisms by which Cox-2 might affect the process of colorectal carcinogenesis. Cyclin D1 is an oncogene that regulates G1 phase progression to S phase of the cell cycle. Its stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…A large number of malignancies have shown overexpression of cyclin D1 such as breast, bladder, lung, pancreatic, and specifically colorectal cancer . Moreover there is growing body of data showing that the association of Cyclin D1 with CRC prognosis . Our data indicated that dorsomorphin decreased the levels of p‐AKT, p‐70s6k, and cyclin D1.…”
Section: Discussionmentioning
confidence: 58%
“…A large number of malignancies have shown overexpression of cyclin D1 such as breast, bladder, lung, pancreatic, and specifically colorectal cancer . Moreover there is growing body of data showing that the association of Cyclin D1 with CRC prognosis . Our data indicated that dorsomorphin decreased the levels of p‐AKT, p‐70s6k, and cyclin D1.…”
Section: Discussionmentioning
confidence: 58%
“…Prostaglandins are upregulated in colorectal cancer, and it was reported that genetic polymorphisms in both COX1 and COX2 are associated with CRC ( 27 , 37 ). COX2 is involved in cell cycle control, and increased expression of COX-2 in CRC patients compared to normal controls indicates its possible role in the progression of CRC ( 40 ). COX2 influences cancer progression by increasing prostaglandin production, preventing tumor cell apoptosis, cell proliferation, and tumor angiogenesis ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…Окрiм згаданого вище, у контекстi p21 особливий iнтерес привертає дволанцюгова активна РНК (p21-saRNA-322), здатна, не задiюючи р53, активувати експресiєю р21 для iндукцiї завершення клiтинного циклу, що може незабаром стати однiєю iз терапевтичних альтернатив лiкування CRC [29]. Згiдно даних дослiджень, висока експресiя р21 корелює iз меншим розмiром пухлини, низьким ступенем злоякiсностi, вiдсутнiстю метастазiв у реґiонарнi лiмфатичнi вузли та вiдсутнiстю або ранньою стадiєю дистантних метастазiв [30], що робить р21 потенцiйним предитором кращого прогнозу при CRC. При цьому у iншому дослiдженнi нi прямого, нi зворотного зв'язку р21 iз стадiєю, ступенем диференцiювання, залученням у пухлинний процес лiмфатичних вузлiв та прогнозом для хворого не виявлено [31].…”
Section: вступunclassified